2012
DOI: 10.1177/1350507612468421
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ views of learning and training for an ageing workforce

Abstract: Abstract:This paper questions how employers view and evaluate the role of learning and training for older workers in light of the increasing number of older workers in the labour market. Learning and training opportunities could be utilised to respond to the 'extending working lives' agenda but interviews with employers suggest that this is not being done. A small number of human resource professionals, managing directors and owners were interviewed to determine what learning opportunities they offered to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
(114 reference statements)
0
17
0
1
Order By: Relevance
“…Arguably this stereotype about the ambitions of older workers could limit the opportunities for those older workers who wanted to progress. As previous research has found, opportunities for older workers to develop and progress may be limited (Beck, 2014; Kroon et al ., 2018). Another manager commented that they tended to promote younger workers: I think the older they get out there, when you say you're doing a good job, I'm thinking of promoting you, they're quite happy doing what they're doing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arguably this stereotype about the ambitions of older workers could limit the opportunities for those older workers who wanted to progress. As previous research has found, opportunities for older workers to develop and progress may be limited (Beck, 2014; Kroon et al ., 2018). Another manager commented that they tended to promote younger workers: I think the older they get out there, when you say you're doing a good job, I'm thinking of promoting you, they're quite happy doing what they're doing.…”
Section: Resultsmentioning
confidence: 99%
“…There are also sectoral and occupational differences in terms of learning and training opportunities, and the value attached to the experience of older workers. For instance, in low-skilled retail jobs, older workers may be seen as not having the ‘right’ attitude, whereas in professional occupations, such as engineering, length of service is valued (Beck, 2014). In terms of organisational size, examples of good practice in age management are often drawn from large supermarket chains, hospitality groups or utility companies – although there are exceptions ( see e.g.…”
Section: Age Management In the Workplacementioning
confidence: 99%
“…Studies regarding the decision to retire find that people with higher incomes and occupational pensions are able to more freely decide when to retire (and tend to be most likely to either retire early or to continue working past SPA), while those without a private pension are more likely to leave work involuntarily, because of redundancy, care-giving responsibilities or ill-health (Phillipson et al 2016 ; Vickerstaff et al 2006 ). There are also differences between those who ‘consider retirement a well-earned entitlement, individuals who retire for health reasons, those who are compelled to continue working for financial reasons and older workers who have an inherently positive relationship with employment and would like to continue working’ (Beck 2014 , p. 201). As such the extending working lives agenda is a complex one, with choice unevenly distributed and constrained by a myriad of interrelated factors (Porcellato et al 2010 ; Lain 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to the question -what learning opportunities were provided for older workers -respondents implicitly conceded that there were only very few educational opportunities for older workers (Beck, 2014). The lack of educational opportunities for older workers is especially regrettable when considering the multitude of potential positive effects.…”
Section: Resultsmentioning
confidence: 99%